Impact of Whole-Body Radiation Dose on Response and Toxicity in Patients With Neuroblastoma After Therapy With (131)I-Metaiodobenzylguanidine (MIBG) - Trieu, Megan (Pediatr Blood Cancer, 2015)
BACKGROUND. (131)I-metaiodobenzylguanidine ((131)I-MIBG) is a targeted radiopharmaceutical for patients with neuroblastoma. Despite its tumor-specific uptake, the treatment with (131)I-MIBG results in whole-body radiation exposure. Our aim was to correlate whole-body radiation dose (WBD) from (131)I-MIBG with tumor response, toxicities, and other clinical factors. METHODS. This retrospective cohort analysis included 213 patients with high-risk neuroblastoma treated with (131)I-MIBG at UCSF Benioff Children’s Hospital between 1996 and 2015. WBD was determined from radiation exposure rate measurements. The relationship between WBD ordered tertiles and variables were analyzed using Cochran–Mantel–Haenszel test of trend, Kruskal–Wallis test, and one-way analysis of variance. Correlation between WBD and continuous variables was analyzed using Pearson correlation and Spearman rank correlation. RESULTS. WBD correlated with (131)I-MIBG administered activity, particularly with (131)I-MIBG per kilogram (P < 0.001). Overall response rate did not differ significantly among the three tertiles of WBD. Correlation between response by relative Curie score and WBD was of borderline significance, with patients receiving a lower WBD showing greater reduction in osteomedullary metastases by Curie score (r(s) = 0.16, P = 0.049). There were no significant ordered trends among tertiles in any toxicity measures (grade 4 neutropenia, thrombocytopenia < 20,000/μl, and grade > 1 hypothyroidism). CONCLUSIONS. This study showed that (131)I-MIBG activity per kilogram correlates with WBD and suggests that activity per kilogram will predictWBD in most patients. Within the range of activities prescribed, there was no correlation between WBD and either response or toxicity. Future studies should evaluate tumor dosimetry, rather than just WBD, as a tool for predicting response following therapy with (131)I-MIBG. Pediatr Blood Cancer 2016;63:436–442.